Experiences with Teaching Nuclear Security Professional Development Courses for Health Physicists - Edward Waller; Jason Timothy Harris; Craig Marianno (International Journal of Nuclear Security, 2016)
Health physicists are professionals that are experts in the recognition, evaluation, and control of health hazards to permit the safe use and application of radiation. They typically have broad knowledge in radiation (ionizing and non-ionizing), biology, ecology and safety. With this wealth expertise we believe the health physicists would be useful partners in an effective security culture. As such over three years, a total of seven professional enrichment courses have been offered by the authors to health physics and radiation protection professionals, both nationally and internationally. Five have been through the Health Physics Society meetings, one through the International Radiation Protection Association meeting, and one at the Massachusetts Institute of Technology. This paper will briefly introduce these courses and will include learning objectives and descriptions of courses’ content. There was limited documented course participant feedback with only 1 of the 7 courses having documented course evaluations. Through both written and verbal feedback to the instructors it was clear the courses were well received.
Keywords: Nuclear Security; Training; Education; Professional Development